Understanding Behavioural Finance: Investor Psychology and Market Anomalies - T. Venkatesan; V. Viswaprakash; R. Alexzander (Journal of Management Studies and Development, 2026)
This study explores the evolving field of behavioral finance, focusing on how psychological factors influence investor decision-making and contribute to persistent market anomalies. Unlike traditional financial theories that assume rational behavior and efficient markets, behavioral finance integrates cognitive biases, emotional influences, and social dynamics to explain deviations from expected market outcomes. The research examines key behavioral concepts such as overconfidence, loss aversion, herding, and framing effects, and their implications for asset pricing, risk perception, and investor behavior. Drawing upon recent empirical and theoretical work from both global and Indian contexts (2020–2025), the study highlights how these psychological elements lead to mispricing and volatility in financial markets. The findings suggest that incorporating behavioral insights can improve investment strategies, regulatory frameworks, and financial literacy programs. By advancing a multidisciplinary approach, this paper contributes to a deeper understanding of real-world financial behavior and calls for more adaptive and inclusive financial systems.